1997
DOI: 10.1097/00006454-199704000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 in neonates with early and late onset infection

Abstract: There are differences in the serum concentrations of IL-6 that can be helpful in detecting early and late onset infection in preterm and term neonates. During the first 48 h of life serial IL-6 determinations are necessary so as not to overdiagnose infection in a neonatal intensive care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
2
7

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 19 publications
4
83
2
7
Order By: Relevance
“…The possibility that earlier diagnosis of sepsis might also improve infant outcome is attractive. Several other markers have been studied in these patients and some seem to be promising (29,(37)(38)(39)(40)(41). The results in the present study suggest that daily CD11b expression measurements might prove useful in the earlier diagnosis of late-onset infection in ELBW infants, but larger multi-center trials with sufficient number of patients are needed to explore potential utility of such markers.…”
Section: Discussionmentioning
confidence: 78%
“…The possibility that earlier diagnosis of sepsis might also improve infant outcome is attractive. Several other markers have been studied in these patients and some seem to be promising (29,(37)(38)(39)(40)(41). The results in the present study suggest that daily CD11b expression measurements might prove useful in the earlier diagnosis of late-onset infection in ELBW infants, but larger multi-center trials with sufficient number of patients are needed to explore potential utility of such markers.…”
Section: Discussionmentioning
confidence: 78%
“…Others have assigned infants with only maternal risk factor(s) for infection to the sepsis group "to develop criteria that are relevant and simple enough for clinical practice" (40 ). In other studies, the presence of two or three categories (by organ system) of clinical signs of infection in the infant has been taken to strongly support a diagnosis of septicemia (41)(42)(43). Absent from neonatology publications, however, are data on just how common a given clinical sign is in all infants ever evaluated (rather than in infants with positive cultures or infants with a specific type of infection).…”
Section: Systemic Response To Infection In Newbornsmentioning
confidence: 99%
“…[5][6][7][8][9] Neither very premature infants or those whose mothers had been exposed to prenatal corticosteroids were included in the study. Ex-vivo sepsis study has shown a decreased IL-6 presence in monocytes of those infants in comparison to term and near-term newborns, and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown sensitivity in the range of 75 to 90% in the first 24 hours of neonatal infection, and an abrupt decrease 48 hours after the beginning of clinical manifestations. [6][7][8][9] Recent studies reported high IL-6 levels in umbilical cord blood in newborns with early-onset sepsis whose mothers had chorioamnionitis. 10,11 However, even though some newborn infants presented neonatal infection, they had low plasma IL-6 levels.…”
Section: Introductionmentioning
confidence: 99%